DIGITAL POSYANDU BERBASIS WEB UNTUK PENINGKATAN PERAN KADER DALAM PENCEGAHAN STUNTING - Ika Kania Fatdo Wardani; Neneng Julianti; Beatrix Elizabeth (JOMIS (Journal of Midwifery Science), 2026)
Stunting is still a chronic nutrition problem in Indonesia, with a national prevalence of 21.5% which still exceeds the WHO threshold (20%), especially in rural areas[1]. Posyandu cadres play an important role in early detection and public education related to stunting prevention. However, the limitations of manual recording and tools are often an obstacle to the effectiveness of the service. This research aims to develop an integrated Digital Posyandu (Web-Based) system to support child health recording and increase cadre capacity in growth screening and nutrition education. The research method uses Research and Development (R&D) with a waterfall system development model and blackbox testing to assess the feasibility of the system. The research population consisted of 90 Posyandu cadres who were given a questionnaire on a Likert scale. The results showed that the level of knowledge of cadres about stunting education was mostly sufficient (83%) and good (10.9%), while knowledge was lacking by 3.3%. Cadres' knowledge of stunting screening is also quite high, which is 82.6% of the adequate category. Cadre perception of the use of the Posyandu digital web showed that 56.7% considered the system useful and 60% considered it easy to use. This system is able to assist cadres in recording growth data, analyzing nutritional status, and digital-based education. It is suggested that the Digital Posyandu be further developed to be applied directly and can be integrated with the national health system